THE EFFECT OF THE ICEBREAKING-ASSISTED TEAMGAMESTOURNAMENT MODEL ON THE STUDENTS’ LEARNING OUTCOMES ON MATHEMATICS IN ELEMENTARY SCHOOL - Hilda Wahyuni; Sapri; Riris Nurkholidah Rambe (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the effects of the TGT (Team Games Tournament) model assisted by Icebreaking on the student’s learning outcomes in mathematics in elementary school. The population of the research involves all of the students in class IV. The sample was selected through a probability sampling technique, which consisted of 24 students for class IV-A as a control class and 24 students for class IV-B as an experimental class. The research used a quantitative method of quasi-experimental design with a pretest and posttest control group design and the instrument used was multiple choice questions to find out the student’s learning outcomes. Hypothesis data analysis was carried out by one-way ANOVA through a computer program of SPSS 21. Based on the results of a one-way variance analysis with a significant degree of 0.05, the value of sig was 0,000 in which 0,000 < 0.05. It implies that the TGT model assisted by Icebreaking had a significant effect. The average score of students’ learning outcomes in the experimental class was 81.3 with a difference between pretest and post-test scores at 51.9. Conversely, the average score of student learning outcomes through the conventional method was 71.8 with a difference between pretest and posttest class control scores at 42.3. Thus, it can be inferred that the application of the TGT (Team Games Tournament) model assisted by Icebreaking is better than the conventional method and there is a significant effect on student learning outcomes in mathematics in elementary school.